Physiological Investigations in Relation to Flowering, Fruit Set and Capsule Developmentj of Cardamom (Elettaria Cardamomum Maton) - Vasantha Kumar K (Department of Plantation Crops and Spices, College of Horticulture, 1986)
Investigations were carried out at the Cardamom Research Station, Pampadumpara and at the College of Horticulture, Vellanikkara during 1982 – ’84 to gather information on the physiological factors governing flowering, fruit set and capsule development of the three popular cardamom cultivars, Malabar, Mysore and Vazhukka. Emphasis had been given to unravel the causes of fruit (Capsule) shedding so as to evolve methods of control. Studies on growth and development in a broad sense depicted that an individual tiller of cardamom had a biennial growth habit. The different aspects of flowering and fruit set studied. Indicated that the variability was high in the Vazhukka cultivar and low in the Mysore cultivar. An early crop bearing habit was exhibited by Malabar, whereas Mysore possessed a late bearing habit and Vazhukka exhibited varying trends. The percentage of fruit set was high in Vazhukka, followed by Malabar and Mysore. Influence of climatic components on the physiology of flowering showed that a distinct dry spell triggered the panicle initiation process. The onset of rain coupled with high temperature was congenial for flower opening. A high soil moisture status combined with a high status of relative humidity (which resulted from a well distributed rainfall) enhanced the setting of capsules. Histological studies conducted in the genotype PV-1 (Malabar) showed that differentiation of panicle primordial was more during November to March. A prominent vascular zonation was observed in the rhizome nodes prior to the initiation of panicle promordia. Histology of the seeds revealed the development of starch grains at the greenish- yellow seed stage. Biological assays for endogenous auxins, inhibitors and cytokinins in the developing capsules indicated a spurt in auxin and cytokinin activity preparatory to fruit set. The level of inhibitory substances rose after the fruit set stage, while that of auxins fell which favoured the formation of an abscission zone causing shedding of immature capsules. Exogenous application of NAA (40 ppm) and 2, 4-D (4 ppm) increased the plant height, enhanced the production of panicles and flowers, reduced dropping of immature capsules and increased the yield. The uptake of nutrients revealed that cardamom is a heavy feeder of potash. The Vazhukka and Malabar cultivars developed less nutrients than the Mysore cultivar for producing unit yield of capsules. Radiotracer studies showed that the photosynthetic efficiency of cardamom was more under low light intensities. The rhizome was found to be the main sink in a cardamom tiller. Gas chromatographic estimation of cardamom oils indicated that the Mysore genotype (PR-107) was superior in quality aspects (because of high content of the esters, alpha terpenyl acetate, geranyl acetate and linalyl acetate) when compared with the Vazhukka genotype (PV-5) and Malabar genotype (PV-1). For consumption as a spice as well as for distillation of the essential oils, the black seed stages (‘karimkai’) was the most idel stage in cardamom.